2019
DOI: 10.3389/fphar.2019.01426
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary, Multicenter, Prospective and Real World Study on the Hemostasis, Coagulation, and Safety of Hemocoagulase Bothrops Atrox in Patients Undergoing Transurethral Bipolar Plasmakinetic Prostatectomy

Abstract: Objective: To evaluate the hemostasis and coagulation effect of Hemocoagulase Bothrops Atrox in benign prostatic hyperplasia (BPH) patients undergoing transurethral bipolar plasmakinetic prostatectomy (TUPKP). Methods: This study adopted a multicenter, prospective, and real world design. BPH patients undergoing TUPKP were divided into two groups according to whether they adopted Hemocoagulase Bothrops Atrox (group B) or not (group A) during perioperative period. The electronic clinical data on every included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Comparative effectiveness research (CER) compares real-world outcomes [51] resulting from alternative treatment options that are available for a given medical condition. Its key elements include the study of effectiveness (effect in the real world), rather than efficacy (ideal effect), and the comparisons among alternative strategies [52].…”
Section: Comparative Effectiveness Researchmentioning
confidence: 99%
“…Comparative effectiveness research (CER) compares real-world outcomes [51] resulting from alternative treatment options that are available for a given medical condition. Its key elements include the study of effectiveness (effect in the real world), rather than efficacy (ideal effect), and the comparisons among alternative strategies [52].…”
Section: Comparative Effectiveness Researchmentioning
confidence: 99%
“…Hemocoagulase agkistrodon does not activate coagulation factor ⅩⅢ, therefore, it is not easy to cause thrombosis. At present, multiple research results indicated that Hemocoagulase agkistrodon was safe and effective for hemostasis by intravenous administration [7,16]. Relevant animal experiments also confirmed that Hemocoagulase agkistrodon does not affect the number of prothrombin and platelets in the blood, and there is no platelet aggregation in normal blood vessels.…”
Section: Discussionmentioning
confidence: 74%
“…Hemocoagulase agkistrodon for injection is an effective drug to reduce perioperative bleeding [16]. It is a hemostatic active ingredient extracted from the venom of Agkistrodon acutus.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocoagulase is one of the most important and indispensable drugs used in surgical operations. Hemocoagulase for Injection is a member of the biological product family, exhibiting a fine hemostasis and coagulation efficacy, which has been widely used as a hemostatic in China ( Li et al, 2019 ). At present, the hemagglutinin drugs on the market in China are mainly isolated from the venom of Bothrops atrox (Baquting ® ), Deinagkistrodon acutus (Suling ® ), Vipera russelli siamensis (Sulejuan ® ), and Agkistrodon halys pallas (Bangting ® ), and their main active ingredients are svTLEs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some svTLEs can also activate plasminogen and induce platelet aggregation ( Castro et al, 2004 ; Sajevic et al, 2011 ). Hemocoagulase atrox for Injection (Reptilase ® and Baquting ® ) isolated from the venom of Bothrops atrox is the earliest and most widely used hemostatic in clinical settings ( Funk et al, 1971 ; Li et al, 2019 ). Hemocoagulase Agkistrodon for Injection (Suling ® ) is isolated from the venom of Deinagkistrodon acutus and contains a single thrombin-like component ( Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%